Effects of Nitrogen Fertilization Levels on the Straw Nutritive Quality of Mr 211 and Mr 219 Rice Varieties - Nori, Hollena (2005)
Rice straw has been used as ruminant feed in many Asean countries although it is regarded as poor quality feed due to its low protein concentration and digestibility. It has been reported that the nutritive quality of rice straw varies among different varieties and is affected by environmental condition that determines its growth pattern. In view of the reports on the environmental effect on straw quality, this study was designed to evaluate the nutritive quality of rice straw with increasing application of nitrogen fertilizer. Samples of rice straw from two varieties, MR 21 1 and MR 21 9 which were grown under five levels of nitrogen fertilizer (0, 120, 160, 200 and 240 kg Nha) were harvested and analyzed for chemical composition and digestibility. The results showed that the straw nutritive quality was improved with nitrogen application. iii Increases in the level of nitrogen fertilization were found to increase the straw crude protein significantly. The maximum nitrogen level at 240 kg N/ha was found to produce crude protein of 8.45%, which is above the level required for ruminant feed. The straw cell wall (NDF) and fiber (ADF) &tion were found to decrease significantly with nitrogen application. The organic matter digestibility was slightly lowered with increasing nitrogen level. The concentration of hemicellulose, cellulose, lignin (ADL), silica, organic matter, ash and the dry matter digestibility were not affected by the nitrogen fertilization level. In the agronomic characteristics and yield components, the level of nitrogen was shown to increase the tiller numbers, stem height, maturity, number of spikelets per panicle, total spikelets per square meter, grain and straw yield and total yield. There were significant varietal differences in the concentration of cell wall (NDF), hemicellulose, cellulose, lignin (ADL) and silica in rice straw, where MR 21 9 had higher cell wall (NDF), hemicellulose and cellulose concentration where as MR 21 1 had higher amount of lignin (ADL) and silica in the straw. In the agronomic characteristics, MR 219 had higher number of tillers per plant, total panicles per square meter, total spikelets per square meter, grain yield, total yield and grain: straw ratio where as MR 21 1 had shorter stem height, maturity period and higher leaf: stem ratio. Both varieties were shown to produce straw with improved nutritive quality. In comparison between the two varieties, MR 219 is superior to MI2 21 1 in view of its higher grain yield and grain: straw ratio. The grain and straw yield were positively correlated with the straw crude protein and digestibility and negatively correlated with the cell wall (NDF) and fiber (ADF) fraction.